2016 IEEE 12th International Conference on Intelligent Computer Communication and Processing (ICCP) 2016
DOI: 10.1109/iccp.2016.7737142
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prevention system against cyber attacks and botnet malware for information systems and Internet of Things

Abstract: The explosion of interconnected devices and the Internet of Things has triggered new important challenges in the area of internet security, due to the various device vulnerabilities and increased potential for cyber-attacks. This paper touches on the areas of Cybersecurity, intrusion detection, prevention systems and artificial intelligence. Our aim is to create a system capable of understanding, detecting and preventing malicious connections using applied concepts of machine learning. We emphasize the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…Based on data provided by the entire environment, the security mechanism assesses the changes in the security posture of the network and plans a defense. In this regard, various data mining and machine learning techniques can provide automated methods to track normal behaviour and flag anomalies [177,178,179]. Moreover, Security Information and Event Management (SIEM) is also considered a vital component of a defense-in-depth approach to network security.…”
Section: Security Analytics It Helps In Gaining Visibility Of Thementioning
confidence: 99%
“…Based on data provided by the entire environment, the security mechanism assesses the changes in the security posture of the network and plans a defense. In this regard, various data mining and machine learning techniques can provide automated methods to track normal behaviour and flag anomalies [177,178,179]. Moreover, Security Information and Event Management (SIEM) is also considered a vital component of a defense-in-depth approach to network security.…”
Section: Security Analytics It Helps In Gaining Visibility Of Thementioning
confidence: 99%
“…Indre and Lemnaru [56] proposed a modular architecture for intrusion detection is proposed which uses network traffic captured as part of the Data Capture Module. The captured network traffic is consumed by three modules employing different detection techniques i.e.…”
Section: Signature Based Approaches To Intrusion Detectionmentioning
confidence: 99%
“…The results showed that the system can detect mirai IoT malware. A solution was proposed in [40] [32]. The approach was built for IoT security that is based on distributed multiagent system.…”
Section: A Rq1:what Are the Contributions Of The Primary Studies?mentioning
confidence: 99%